The Effect of Promotion Through Utilization of Social Media Instagram Account @Bengkulu_Guitar on Guitar Purchase Decisions (At Bengkulu Guitar on Jalan Kalimantan, Kota Bengkulu) - Al Iqsan Dwi Prajayu; Eti Arini (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the effect of promotion through the use of the Instagram account @bengkulu_gutar on the purchase decision of a guitar at Bengkulu Guitar on Jalan Kalimantan, Bengkulu City. The sample in this study were 99 consumers who made purchases of guitars at Bengkulu Guitar. The data collection technique used a questionnaire. The analysis technique used is simple linear regression, coefficient of determination and hypothesis testing. The results showed the results of linear regression with the equation Y = 25.939 + 0.482X. This means that if X (promotion through the use of social media Instagram) has increased by one unit, then Y (economic activity) will increase by 0.482 times. The coefficient of determination of the R square is 0.254. This means that promotion through the use of Instagram social media has an influence on purchasing decisions by 25.4% while the rest (100-25.4% = 74.6%) is influenced by other causal factors which were not examined in this study. Promotion through the use of social media Instagram has a significant effect on purchasing decisions (Y) at Bengkulu Guitar, this is evidenced by hypothesis testing which shows a significant value (sig α = 0.000 <0.05). This means that H_0 is rejected and H_a is accepted